SHELF LIFE PREDICTION OF THE SNAKEHEAD BISCUIT (Ophiocephalus striatus) USING ACCELARATED CRITICAL MOISTURE METHODE, MODEL OF LABUZA - Murni, Septia; Karnila, Rahman; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted to determine shelf life of the biscuit rapidly andmore simply with accelarated critical moisture methode model of Labuza.Onresearch, biscuit was ditinguished into B0 (without the powder of snakehead) andB1 (subtituted by the powder of snakehead). The nutrition facts of the biscuitswere: protein (8,09% of B0 and 24,02% of B1), fat (21,33% of B0 and 53,16% ofB1), ash (1,14% of B0 and 1,54% of B1), and mositure (1,96% of B0 and 5,39%of B1). The biscuits were stored in polypropylen packaging. The variabels ofmodel of Labuza: 1) The main parameters; Mi (0,051g H2O/g solid of B0 and0,062g H2O/g solid of B1), Mc (0,066 g H2O/g solid of B0 and 0,078 g H2O/gsolid of B1), Me (0,601 g H2O/g solid of B0 and 0,576 g H2O/g solid of B1);2)The supporting parameters; curve slope (b) (0,224 of B0 and 0,422 of B1), k/x(0,002 g H2O/m3.day), A/Ws (0,0004 m2/g), and P0 (31,824 mmHg). According tomodel of Labuza, shelf life of the bicuits were stored in room temperature (30oC)and RH 90% were 8,14 months for B0 and 17,54 months for B1. Different shelflife of two biscuits were caused by the difference of moisture value (Mi, Mc, Me).The high hygroscopic protein (albumin) of B1 caused the slowed water difution(need many days) to reach the equilibrium condition.Kata Kunci : Shelf life, biscuit, snakehead, moisture, model of Labuza